Simulación molecular de isotermas de adsorción para hidratos simples de metano y dióxido de carbono - F. Castillo-Borja (Revista Mexicana de Física, 2016)
In this work the hydration number and fractional cage occupancy of simple methane and carbon dioxide sI clathrate hydrates are calculated by Monte Carlo simulations. The results are compared with experimental data and those obtained by applying the theory of van der Waals and Platteeuw, which combined statistical thermodynamics with the classical theory of adsorption. The hydration numbers estimated from both methodologies are within the range of experimental values for the two hydrates. The fractional cage occupancy obtained by Monte Carlo simulations for methane hydrate agrees on the trend with those calculated using the theory of van der Waals and Platteeuw. In the case of carbon dioxide hydrate, the occupation of cavities reaches two plateaus in pressure that may be due to that large cages are occupied first and then, when the pressure increases the small cages begin to be occupied.